AR-NGEUNA 4.0 testing: Augmented reality application for Sundanese traditional food - Yulia, Cica (INVOTEC, 2023)
The advancement of Augmented Reality (AR) technology has opened up new opportunities in the development of innovative learning tools. In this scientific paper, we conducted a testing of the "AR-Ngeuna 4.0" application specifically designed for learning West Javanese traditional cuisine. The research design used in this study was cross-sectional with the Technology Acceptance Model (TAM) approach. The research results indicate that the majority of respondents rated the perceived ease of use and perceived usefulness of the "AR-Ngeuna 4.0" application as highly appropriate for learning traditional cuisine. Users' attitudes toward using the application and their behavioral intention to continue using it also received positive responses. The assessment of user awareness in utilizing the application (Actual System Usage) was also favorable. Therefore, the "AR-Ngeuna 4.0" application is deemed suitable for use as a learning tool for traditional cuisine by students in Vocational High Schools, especially in the Culinary Arts Program.